PERANAN GURU PAI DALAM PEMBINAAN AKHLAKUL KARIMAH DI SMPI DARUS SA’ADAH PONCOKUSUMO - Mas Imam Roji; Khoirul Asfiyak; Imam Safi’i (Vicratina : Jurnal Ilmiah Keagamaan, 2021)
The development of morality in Islam is a very important process in life, whether it is within the scope of the family or the wider community in general. This is the background for carrying out descriptive research on what morality is, what things can accelerate a teacher in fostering the morals of students, and what things can hinder a teacher from fostering the morals of students at SMPI Darussa'adah Poncokusumo . This research began on May 10-14, 2021. The research in a subject is the teacher, especially PAI teachers, and student. This study uses qualitative research techniques in order to understand what phenomena are the research subject are experienced. The result of the research include: 1) the moral condition of the students, 2) the causal factors that influence the development of morality, 3) the solution of the PAI teacher in dealing with the causes of the failure to foster the morals of the students. Kata kunci : Guru Pai, Akhlakul Karimah